Radiation Tolerance of Pseudanabaena catenata, a Cyanobacterium Relevant to the First Generation Magnox Storage Pond - Foster, Lynn; Muhamadali, Howbeer; Boothman, Christopher; Sigee, David; Pittman, Jon K.; Goodacre, Royston; Morris, Katherine; Lloyd, Jonathan R. (Frontiers in Microbiology, 2020)
Recently a species of Pseudanabaena was identified as the dominant photosynthetic organism during a bloom event in a high pH (pH ~11.4), radioactive spent nuclear fuel pond (SNFP) at the Sellafield Ltd. UK facility. The metabolic response of a laboratory culture containing the cyanobacterium Pseudanabaena catenata, a close relative of the major photosynthetic microorganism found in the SNFP, to X-ray irradiation was studied to identify potential survival strategies used to support colonisation of radioactive environments. Growth was monitored and the metabolic fingerprints of the cultures, during irradiation and throughout the post-irradiation recovery period, were determined using Fourier transform infrared (FT-IR) spectroscopy. A dose of 95 Gy delivered over 5 days did not significantly affect growth of P. catenata, as determined by turbidity measurements and cell counts. Multivariate statistical analysis of the FT-IR spectral data revealed metabolic variation during the post irradiation recovery period, with increased polysaccharide and decreased amide spectral intensities. Increases in polysaccharides were confirmed by complementary analytical methods including total carbohydrate assays and calcofluor white staining. This observed increased production of polysaccharides is of significance, since this could have an impact on the fate of the radionuclide inventory in the pond via biosorption of cationic radionuclides, and may also impact on downstream processes through biofilm formation and biofouling.